Enhancing the in vivo stability of polycation gene carriers by using PEGylated hyaluronic acid as a shielding system - Jiaxue Liu; Xiaoli Bao; Irina Kolesnik; Boyan Jia; Zihan Yu; Caiyun Xing; Jiawen Huang; Tingting Gu; Xiaotong Shao; Alexey Kletskov; Andreii S. Kritchenkov; Vladimir Potkin; et al. (BIO Integration, 2022)
To increase the in vivo stability of cationic gene carriers and avoid the adverse effects of their positive charge, we synthesized a new shielding material by conjugating low molecular weight polyethylene glycol (PEG) to a hyaluronic acid (HA) core. The HA-PEG conjugate assembled with the positively charged complex, forming a protective layer through electrostatic interactions. DNA/polyetherimide/HA-PEG (DNA/PEI/HA-PEG) nanoparticles had higher stability than both DNA/polyethyleneimine (DNA/PEI) and DNA/PEI/HA complexes. Furthermore, DNA/PEI/HA-PEG nanoparticles also showed a diminished nonspecific response toward serum proteins in vivo. The in vivo transfection efficiency was also enhanced by the low cytotoxicity and the improved stability; therefore, this material might be promising for use in gene delivery applications.